Secrecy rate optimization for SWIPT in two‐way relay networks with multiple untrusted relays and channel estimation errors - Dayong Yang; Mo Zhang; Biao Wan; Nanrun Zhou (IET Communications, 2021)
Abstract The secrecy rate of two‐way untrusted relay networks with imperfect channel state information based on SWIPT is investigated when multiple relays harvest energy from two sources. Despite assisting in information forwarding, the relays are considered untrusted in that they might attempt to eavesdrop on confidential information. To interfere with eavesdropping by untrusted relays, sources‐based friendly cooperative jamming is introduced. A joint power allocation and time switching strategy has been studied to maximize the sum secrecy rate of the system under total block transmission duration and power constraints. The genetic algorithm (GA) is introduced to optimize the proposed joint power allocation and time switching (JPTs) scheme. In addition, two suboptimal schemes are proposed: the power allocation and time switching scheme for individual power constraints and the power allocation scheme for equal time allocation. Simulation results demonstrate that the proposed joint power allocation and time switching strategy performs better in contributing to the total secrecy rate of the system.